2022
DOI: 10.1007/s00500-022-07535-5
|View full text |Cite
|
Sign up to set email alerts
|

No-reference image quality assessment with multi-scale weighted residuals and channel attention mechanism

Abstract: Image is an important information source for human perception and machine pattern recognition. Image quality determines the accuracy and sufficiency of the information obtained. With the rapid development of deep learning in image processing, no-reference image quality assessment (NR-IQA) plays a significant role. Currently, most NR-IQA methods mainly use the global features of images without paying attention to the detail-rich local features and the dependencies between channels. There are subtle differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…With respect to the design of network structure, we adopt different network structures for different datasets. In our experiments, we found that it is not true that the more complex the model structure, the higher the quality of the generated adversarial examples [56,57] . Based on this principle, the network structures we designed for the three datasets, MNIST, Fashion-MNIST, and CIFAR10, are given in Table 1.…”
Section: Network Structure Design For Three Datasetsmentioning
confidence: 79%
“…With respect to the design of network structure, we adopt different network structures for different datasets. In our experiments, we found that it is not true that the more complex the model structure, the higher the quality of the generated adversarial examples [56,57] . Based on this principle, the network structures we designed for the three datasets, MNIST, Fashion-MNIST, and CIFAR10, are given in Table 1.…”
Section: Network Structure Design For Three Datasetsmentioning
confidence: 79%
“…Following refs. [15,27,35,36], our training strategy involves non-overlapping cropping of images input into the network into blocks of size 32 × 32. The quality scores for each image block were inherited from the original image.…”
Section: Implementation Detailsmentioning
confidence: 99%